2017
DOI: 10.1002/jcp.25724
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin Induces IL‐6 and MCP‐1 Production via Toll‐Like Receptor 4 Signaling in Human Gingival Fibroblasts

Abstract: Calprotectin, a heterodimer of S100A8 and S100A9 molecules, is associated with inflammatory diseases such as inflammatory bowel disease. We have reported that calprotectin levels in gingival crevicular fluids of periodontitis patients are significantly higher than in healthy subjects. However, the functions of calprotectin in pathophysiology of periodontitis are still unknown. The aim of this study is to investigate the effects of calprotectin on the productivity of inflammatory cytokines in human gingival fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…(29) and ultimately trigger the production of pro-inflammatory cytokines (30). Depending on the system, calprotectin has been detected both upstream (31) and downstream (32) of IL-6, which has emerged as a possible therapeutic target in COVID-19. Calprotectin is also a potent stimulator of neutrophils themselves, promoting degranulation and phagocytosis (33,34), as well as other more recently described effector functions such as neutrophil extracellular trap (NET) release (35).…”
Section: Discussionmentioning
confidence: 99%
“…(29) and ultimately trigger the production of pro-inflammatory cytokines (30). Depending on the system, calprotectin has been detected both upstream (31) and downstream (32) of IL-6, which has emerged as a possible therapeutic target in COVID-19. Calprotectin is also a potent stimulator of neutrophils themselves, promoting degranulation and phagocytosis (33,34), as well as other more recently described effector functions such as neutrophil extracellular trap (NET) release (35).…”
Section: Discussionmentioning
confidence: 99%
“…Narumi et al () reported that natural killer (NK) cells are activated via calprotectin‐RAGE signaling, and calprotectin‐induced NK cell activation may be useful for cancer immunotherapy. Importantly, human oral epithelial cells constitutively express both TLR4 mRNA and RAGE mRNA, whereas HGFs express TLR4 mRNA constitutively, but not RAGE mRNA (Nishikawa et al, ). These results indicate that TLR4 may be the main target receptor for calprotectin in HGFs.…”
Section: Effects Of Inflammation‐related Factors On Il‐6 Production Imentioning
confidence: 99%
“…In addition, significant elevation of calprotectin (CPT), a heterodimer of S100A8 and S100A9, are found in inflamed periodontal tissues [7]. Our previous findings showed that CPT induces not only IL-6 production in HGFs [12], but also sIL-6R production in THP-1 macrophages [7], resulting in progression of periodontitis by induction of IL-6 cascades. Furthermore, vascular endotherial growth factor (VEGF) is a significant factor for diabetic complications, and is implicated in the development of neovascularization and endotherial dysfunction in diabetic retinopathy [13].…”
Section: Introductionmentioning
confidence: 99%